2009
DOI: 10.1002/jor.20928
|View full text |Cite
|
Sign up to set email alerts
|

Knee kinematics in medial osteoarthritis during in vivo weight‐bearing activities

Abstract: Dynamic knee kinematics were analyzed for medial osteoarthritic (OA) knees in three activities, including two types of maximum knee flexion. Continuous x-ray images of kneeling, squatting, and stair climbing motions were taken using a large flat panel detector. CT-derived bone models were used for the model registration-based 3D kinematic measurements. Three-dimensional joint kinematics and contact locations were determined using two methods: bone-fixed coordinate systems and by interrogation of CT-based bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 45 publications
5
69
0
Order By: Relevance
“…The differences might be due to variations in activities, choice of coordinate systems, and preoperative pathological changes. 13,18,22,23,39 After PCR-TKAs, we did not observe the characteristic internal tibial rotation between full extension and 30…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The differences might be due to variations in activities, choice of coordinate systems, and preoperative pathological changes. 13,18,22,23,39 After PCR-TKAs, we did not observe the characteristic internal tibial rotation between full extension and 30…”
Section: Discussionmentioning
confidence: 67%
“…Other studies also reported less posterior translation in OA compared to normal knees. 13,18,22 In PCR-TKA knees, the reduction of posterior femoral translation was been reported by many studies. 13,24,25 For example, Kitagawa et al observed posterior translation of the lateral condyle from full extension to maximum flexion reduced from 9 ± 1 mm for OA knees to 5 ± 0 mm for TKA knees.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This difference at this gait phase, which corresponds to maximal knee extension, may be due to the lack of full extension of OA knees. Hamai et al, evaluated rotational angles using CT and reported a femoral internal rotation bias compared with the control group [3]. Saari et al, using dynamic radiostereometric analysis (RSA), found a decreased internal rotation in the knee OA group.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative kinematic analysis is an important tool for a thorough understanding of joint function [1]. Kinematics of osteoarthritic (OA) knees has been evaluated using surgical navigation systems, magnetic resonance imaging (MRI) and computed tomography (CT) [2][3][4], but these techniques cannot be used to study weight-bearing activities, and their results may be therefore be affected. With advances in sophisticated motion-capture technology, 3D knee motion during weightbearing is now available.…”
Section: Introductionmentioning
confidence: 99%